2023
DOI: 10.1002/prca.202200118
|View full text |Cite
|
Sign up to set email alerts
|

Urinary collagen peptides: Source of markers for bone metabolic processes in kidney transplant recipients

Abstract: Introduction: Kidney transplant recipients (KTRs) are at an increased risk of fractures.Total urinary hydroxyproline excretion served as marker for bone resorption (BR) but was replaced by β-CrossLaps (CTX), a C-terminal collagen α-1(I) chain (COL1A1) telopeptide. We investigated the low-molecular-weight urinary proteome for peptides associated with changes in bone metabolism after kidney transplantation. Methods: Clinical and laboratory data including serum levels of CTX in 96 KTR from two nephrology centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 104 publications
1
5
1
Order By: Relevance
“…Consistent with previous studies [3][4][5][6][7][8] , our observed bone peptide fragment products were rich in hydroxyproline residues and more frequently observed and at higher abundance in urine versus serum. The products spanned a wide range in molecular weight (174-1540 Da), from di-peptides to peptide fragments comprising 17 amino acid residues (Table 1).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous studies [3][4][5][6][7][8] , our observed bone peptide fragment products were rich in hydroxyproline residues and more frequently observed and at higher abundance in urine versus serum. The products spanned a wide range in molecular weight (174-1540 Da), from di-peptides to peptide fragments comprising 17 amino acid residues (Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…Amongst the COL1A1 specific products, two overlapped with the sequences of previously reported urine COL1A1 fragments and one reproduced exactly another previously reported fragment. 5 Three of the COL1A1-specific resorption products are not previously described. Six of the seven highest molecular weight products did not map to known COL1A1 protease cleavage sites, potentially indicating new COL1A1 proteolytic degradation pathways.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations